Dynamic global careers: a new conceptualization of expatriate career paths. Issue 2 (6th March 2017) - McNulty, Yvonne; Vance, Charles M.
Abstract : Purpose: Most studies of expatriates have explored global careers as unfolding within assigned or self-initiated expatriation contexts in a predominantly linear fashion. The purpose of this paper is to conceptualize that expatriates' career progression is facilitated by frequent moves between domains, with an increasing overlap among assigned-expatriate (AE) and self-initiated expatriate (SIE) contexts. Design/methodology/approach: Underpinned by findings from extant literature, the authors review and integrate studies of expatriation and careers to conceptualize an AE-SIE career continuum. Findings: The authors debunk the idea that AEs and SIEs are a type of expatriate per se, but instead is indicative only of their career orientation in terms of where they choose to sit on the AE-SIE career continuum at any point in time. Specifically, individuals pursuing global careers in international labor markets include up to eight types of expatriate who retain varying degrees of AE vs SIE characteristics dependent on the point they choose along the continuum. Practical implications: The tension that dynamic global careers cause for multinational enterprises (MNEs) is not necessarily "bad", and that by accepting and accommodating changes in career orientation MNEs will be able to make clearer and more consistent global staffing decisions. Originality/value: The authors provide a new, improved conceptualization of linear and non-linear global careers and of the challenges global career actors face throughout their career development both at home and abroad. They further show that while career orientation explains why expatriates engage in various types of international work experiences, their typology adds explication of the various types of expatriate who pursue global careers.